Radial optic neurotomy: a new surgical approach for glaucoma treatment? - Rosenstein, Ruth Estela (2012)
Glaucoma is a leading cause of blindness worldwide, characterised by specific visual field defects due to the degeneration of retinal ganglion cells and damage to the optic nerve head (ONH). Elevated intraocular pressure (IOP) is the most important risk factor for glaucoma development. One of the clinical hallmarks of glaucomatous optic neuropathy is the excavation of the ONH, which consists of a progressive posterior displacement of the ONH surface and excavation of the pre-laminar tissues beneath the anterior-most aspect of the scleral canal, known as the anterior scleral ring. Radial optic neurotomy (RON) is a surgical technique that has been proposed for treating central retinal vein occlusion. While the original rationale of RON was the relief of increased tissue pressure within the optic nerve that results from occlusion of the central retinal vein, recent results are discussed here which suggest that by relaxing of the scleral ring of the prelaminar and laminar regions of the ONH, RON may alleviate the IOP-related connective tissue stress, and in turn, prevent the onset and reduce the progression of glaucomatous neuropathy.